Wavelet Analysis of Coherent Structures Above Maize and Soybean Crops - Curto, Lucia; Gassmann, María I. (Boundary-layer meteorology, 2022)
Turbulent coherent structures developed in the atmospheric surface layer are responsible for a large part of momentum and scalar fluxes exchanged with canopy layers. Their participation in processes such as evapotranspiration, pathogen infections, mechanical damage due to wind gustiness, modifies crop yield, with generally negative effects. Although South America has a variety of land covers, studies of these subjects are not common in the region. Here, we characterize the time scales of turbulent coherent structures above extensive maize and soybean crops using the wavelet methodology. The role of canopy-height changes associated with crop growth on turbulent structures development is analyzed. The effect of atmospheric stability on the characteristics of the structures detected is also studied. Wavelet analysis shows that both momentum and sensible heat are transported mostly by eddies of 350–400 s periods and also by more intense eddies of 40–50 s period. For momentum fluxes, the former period range prevails under strongly unstable conditions, while the second is present mostly under near-neutral situations. On the contrary, 40–50 s-lasting structures dominate the sensible heat transport under free convection conditions, while longer-lasting eddies transport heat in near-neutral conditions. Stability is the main factor allowing the coherent-structure topological classification, while the crop height is not important. Structures are identified through measurements performed at relative heights greater than those usually discussed in the literature, which indicates the need for further research into coherent-structure modelling.